European urban sprawl - Pichler-Milanović, Nataša (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
This paper has its origins in a comparative research project examining aspects of urban sprawl in Europe undertaken within the 5.FP EU. The project Urban Sprawl: European Patterns, Environmental Degradation and Sustainable Development (URBS PANDENS EVK4-CT- 2001-00052) sought to understand recent trends in urban sprawl in a number of case study urban regions and to advise the European Commission on policy development with regard to the control, management and amelioration of the effects of urban sprawl.
Keywords: urbana geografija; mesta; urbani razvoj; prostorski razvoj; urbanizacija; sonaravni razvoj; Europe; Evropa